A micro-computed tomography (micro-CT) analysis of postmenopausal osteoporotic rat models supplemented with ficus carica - Mohammad A.; Razaly N.I.; Rani M.D.M.; Muhammad Shamsir Mohd Aris; Dom S.M.; Effendy N.M. (Open Science Publishers LLP Inc., 2024)
Indexed by SCOPUS